Hubungan Tingkat Pengetahuan Dan Dukungan Keluarga Dengan Keaktifan Kontrol Pada Penderita Hipertensi Di Wilayah Puskesmas Gatak Kabupaten Sukoharjo - Siswanto, Mahfudz Bayu Purnomo, Arina Maliya, S.Kep., M.Si., Med, Dewi Suryandari , S.kep., Ns (2015)
Activeness for routine control of hypertension patients currently still considered low. Most patients with hypertension tend to ignore the therapy program for no negative effects or complications of the disease they experienced. Liveliness someone to do the control is influenced by the knowledge that we know the knowledge is very important in order for someone to stick controls so that no complications in patients with hypertension. Family support can be a very influential factor in determining the treatment program, because the family serves as a support system for members who suffer from hypertension. This study aimed to determine the relationship of the level of knowledge and support for families with liveliness control in patients with hypertension in the PHC Gatak Sukoharjo. This study design with cross cross-sectional approach. The population in this study were all patients with hypertension in Sukoharjo Gatak Regional Health Center in 2013, amounting to 987 people, sampling technique used was simple random sampling, so that the sample taken is 91 to be the respondent. The analytical tool used by the Chi-square test (2). The results reveal that: 1) there is a significant relationship between the level of knowledge to control the activity of hypertension patients in the health center Gatak Sukoharjo; 2) there is a significant relationship between family support with the activity of the control patients with hypertension in the PHC Gatak Sukoharjo